1992
DOI: 10.1007/bf02637677
|View full text |Cite
|
Sign up to set email alerts
|

Densities of vegetable oils and fatty acids

Abstract: Complete data for density as a function of temperature have been measured for a number of vegetable oils (crambe, rapeseed, corn, soybean, milkweed, coconut, lesquerella), as well as eight fatty acids in the range C9 to C22 at temperatures from above their melting points to 110°C (230°F). The specific gravity and density measurements were performed according to American Society for Testing and Materials (ASTM) standard test methods D 368, D 891 and D 1298 for hydrometers and a modified ASTM D 369 and D 891 for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
95
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(109 citation statements)
references
References 4 publications
11
95
0
1
Order By: Relevance
“…Viscosity increased with the molecular weight and decreased with increasing unsaturated level and high temperature (Nourrechni et al, 1992). The viscosity of the oil (Nigerian Jatropha seed) was found to be higher than the Indian Jatropha seed oil.…”
Section: Resultsmentioning
confidence: 89%
“…Viscosity increased with the molecular weight and decreased with increasing unsaturated level and high temperature (Nourrechni et al, 1992). The viscosity of the oil (Nigerian Jatropha seed) was found to be higher than the Indian Jatropha seed oil.…”
Section: Resultsmentioning
confidence: 89%
“…It increases with the molecular weight of the oil and decreases with increasing unsaturation and high temperature [44]. The viscosity of Shea butter was 83.92cSt (centi stokes) at 40°C.…”
Section: Viscosity (Vs)mentioning
confidence: 96%
“…Lang et al [25] and Noureddini et al [26] also reported that the viscosity of canola and other vegetable oils decreases with an increase in temperature.…”
Section: Base Fluid Viscositymentioning
confidence: 97%